PENGEMBANGAN HANDOUT PENGAJARAN WRITING II BERBASIS PROCESS GENRE-BASED APPROACH UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS DALAM PENULISAN TUGAS AKHIR (Jurnal Pelangi : Research of Education and Development, 2014)
This article is a developmental research that aims to develop teaching materials based on the writing process in producing genre. In this study also estimated the validity of teaching materials developed. This research method was done in four stages; definition, design, development and dissemination. Definition was done to analyze the syllabus of Writin II. Design was done to analyze the need asse students and teachers. The result of the need analysis for both students and teachers indicated that they need writing teaching material which can lead them to pass the process of writing. Development results demonstrate the validity of the product contained in the category can be used with a slight improvement with a value of 75.4. It can be concluded that the product can be used as teaching materials to teach writing. Dissemination was done in limited trial.